Entrepreneurship and entrepreneurial intention in Administration students of Public Universities of the Macro region of Southern Peru (Revista Innova Educación, 2020)
Objective: To determine the level of entrepreneurial activities and entrepreneurial intention of Administration students of Public Universities of the Southern Macro region of Peru. Method: It uses the integral model of entrepreneurial intention of Schalaegel and Koening, quantitative approach, non-experimental design, descriptive and correlational level; survey and documentary techniques; population 2508 and shows 295 students. Results: The promotion of entrepreneurship activities is high in business ideas, entrepreneurship fairs; and low participation in competitions of prototypes and inventions. According to the Chi-square calculated for each indicator both are significant; however, the perceived desirability has a Cramer V of 0.886 higher than that calculated for the perceived viability; This allows to deduce the perceived desirability is more strongly related to the intention of entrepreneurship.
Keywords: Entrepreneurship; entrepreneurial intention; entrepreneurial universities